The Effect of Internal Control, Accounting Rule Compliance, Information Asymmetry, Opportunity and Management Morality on Fraud Tendency - Ernawatiningsih, Ni Putu Lisa; Suryandari , Ni Nyoman Ayu (Jurnal Akuntansi Profesi, 2025)
Fraud is a deliberate deception that causes losses without the injured party realizing it and provides benefits for the perpetrator of the fraud. The study aims to determine the effect of internal control, compliance with accounting rules, opportunity, information asymmetry and management morality on the tendency of fraud. The population in this study were all employees of the Village Credit Institution in Ubud District and the sample selection was carried out using the purposive sampling method so that a sample of 96 respondents was obtained. The data used in this study were primary data with data collection techniques by distributing questionnaires to research respondents. Data analysis was carried out using multiple linear regression analysis. The results of the study showed that internal control, compliance with accounting rules and management morality had a negative and significant effect on the tendency of fraud in LPDs in Ubud District. Information asymmetry had a positive and significant effect on the tendency of fraud in LPDs in Ubud District. Meanwhile, the opportunity does not affect the tendency of fraud in LPD in Ubud District.